SISTEM PENYIRAMAN TANAMAN OTOMATIS BERBASIS ARDUINO - Herawati, Rosita; Putranto, Yulianto Tejo (PROXIES, 2013)
This paper discusses the automatic plant watering system, a simple but useful by using Arduino. Watering systems based on sensor readings at a planting medium (soil), which is read by the Arduino. The sensor detects the level of humidity and dryness of the planting medium. Arduino connected to a relay system that will disconnect or connect the electrical cu"ent of the solenoid valve. Thus, at a certain level of dryness or humidity, the solenoid valve opens, and the watering process takes place. The level of dryness of the media obtalnedfrom the initial experiment Keywords: Ardulno, automatic watering, dryness sensor